2010
DOI: 10.4161/cc.9.8.11252
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell dynamics in mouse hair follicles: A story from cell division counting and single cell lineage tracing

Abstract: Understanding tissue stem cell behavior is a prerequisite for elucidating the mechanisms that govern their self-renewal and differentiation. Previously, we provided single cell lineage tracing and proliferation history data (based on H2B-GFP label dilution over time) in mouse hair follicles. We proposed a population deterministic model with symmetric stem cell fate decisions throughout life. Here we provide data suggesting that in hair follicle stem cells the self-renewing divisions within the niche (bulge) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
6
34
0
1
Order By: Relevance
“…However, it has been debated whether these cells truly represent long-lived stem cells. In mice, the hair follicle bulge harbours the most pluripotent stem cells and lineage tracing experiments in this system suggest that symmetric divisions replenish these cells (Petersson et al, 2011;Zhang et al, 2010). This is consistent with findings that hair follicle stem cells do not oblige with the 'immortal strand' hypothesis (Sotiropoulou et al, 2008;Waghmare et al, 2008).…”
Section: Asymmetric Divisions and Cell Fate Determination: Outstandinsupporting
confidence: 76%
See 1 more Smart Citation
“…However, it has been debated whether these cells truly represent long-lived stem cells. In mice, the hair follicle bulge harbours the most pluripotent stem cells and lineage tracing experiments in this system suggest that symmetric divisions replenish these cells (Petersson et al, 2011;Zhang et al, 2010). This is consistent with findings that hair follicle stem cells do not oblige with the 'immortal strand' hypothesis (Sotiropoulou et al, 2008;Waghmare et al, 2008).…”
Section: Asymmetric Divisions and Cell Fate Determination: Outstandinsupporting
confidence: 76%
“…This proposes that stem cells asymmetrically segregate their chromosomes to retain the same strand of DNA over several divisions in order to avoid accumulating DNA mutations. Progenitors located just below the bulge in the hair germ (Greco et al, 2009) can divide asymmetrically (Zhang et al, 2010) and some recent evidence suggest that these cells replenish bulge stem cells while at the same time providing enough cells to drive anagen hair follicle growth (Hsu et al, 2011) (Fig. 4).…”
Section: Asymmetric Divisions and Cell Fate Determination: Outstandinmentioning
confidence: 99%
“…; P=0.42, Mann-Whitney U-test) in the number of labeled follicles from 3 days to 6 months post induction (supplementary material Fig. S2F), consistent with a model in which most or all HF bulge cells possess stem cell potential but are occasionally lost from the stem cell niche, as previously described by others (Hsu et al, 2011;Zhang et al, 2010).…”
Section: Gc/gcsupporting
confidence: 68%
“…1, B and C). Clonal analysis of bulge SCs indicated that some bulge SCs can differentiate into all HF lineages, whereas others are com mitted to either the outer or the inner cell layers (Legué et al, 2010;Zhang et al, 2010). These results suggest that the hetero geneity in the differentiation potential of bulge SCs is either related to an intrinsic heterogeneity of bulge cells containing multipotent and unipotent SCs or through a regulation of the lineage differentiation potential of multipotent SCs.…”
Section: Introductionmentioning
confidence: 83%